Comparison and analysis about 5G indoor new coverage solutions - Yanlei CHEN; Junxian MENG; Wei LIU; Xun WANG (Dianxin kexue)
5G has entered the stage of scale deployment, and indoor is one of the key scenes.With the evolution of new technology, indoor new coverage solutions emerge in endlessly, such as RRU/pRRU+RF power amplifier, multi-channel joint transceiver technology, frequency conversion system, etc.Compared with the traditional compartment coverage scheme, new coverage solutions have the characteristics of low cost and good performance.The technical principle, basic performance, key problems and industrial status of the new coverage solutions were innovatively and comprehensively analyzed, and the corresponding target scenarios and deployment suggestions were summarized through actual pilot verification.